Pelaksanaan Yurisdiksi Universal Terhadap Modern Piracy Jure Gentium - Nadiyah Asfarosya (JURNAL BELO, 2020)
This study aims to analyze the relevance of the approach of universal jurisdiction in law enforcement against the crime of modern pirates. This study looks at piracy itself which changes over time and the effectiveness of universal jurisdiction in minimizing back piracy that can affect the international community. This research is normative. Universal jurisdiction has long been in law enforcement against piracy. However, turning the numbers of countries implementing universal jurisdiction raises the question of what constitutes an obstacle to implementing universal jurisdiction over the crime of piracy. In addition, several solutions have emerged that are considered more effective in enforcing the law against modern piracy in order to prevent the culture of impunity.